Lender Screening and the Role of Securitization: Evidence from Prime and Subprime Mortgage Markets - Keys, Benjamin J.; Seru, Amit; Vig, Vikrant (Review of Financial Studies, 2012)
This article examines the link between mortgage securitization and lender screening during the boom and bust of the U.S. housing market. Using comprehensive data on both prime and subprime securitized and bank-held loans, we provide evidence that securitization affected lenders' screening decisions in the subprime market for low-documentation loans through two channels: the securitization rate and the time it takes to securitize a loan. The change in decision-making by subprime lenders occurs on dimensions that are unreported to investors. Examining the time-series evolution of the securitization market further reinforces these findings. We exploit heterogeneity across subprime and prime markets to illustrate that the potential for moral hazard may be reduced with greater collection of hard information and increased monitoring of lenders. Our results suggest that the policy debate regarding securitization and lenders' underwriting standards should separately evaluate the agency and non-agency markets, with special attention toward the extent of soft information in assets being securitized.